Biopriming of seed with plant growth-promoting bacteria for improved germination and seedling growth - Fiodor, Angelika; Ajijah, Nur; Dziewit, Lukasz; Pranaw, Kumar (Frontiers in Microbiology, 2023)
Several seed priming methods can be used to improve seed germination, seedling vigour, and to overcome abiotic stress. In addition to these benefits, only the biopriming method provides the additional benefit of biotic stress management, earning it special attention. Seed biopriming is useful in almost all crops around the world and is an environmentally friendly alternative to chemical fungicides. Biopriming usually refers to use of beneficial microorganisms, in particular plant growth-promoting bacteria (PGPB) able to survive under various harsh environmental conditions. In this study various bacterial strains were isolated from samples of different origins i.e. rhizospheric soil, desert sand, and sea mud. Preliminary screening of 156 bacterial isolates was conducted on the basis of their potassium (K), phosphorus (P) solubilization ability and production of plant growth hormone i.e. indole acetic acid (IAA). The most efficient bacteria were identified by 16S rRNA gene nucleotide sequences and further examined for their ACC deaminase activity, ammonia production, biocontrol activity (defined via chitinolytic activity, HCN and siderophores production). Finally, carrot seed germination assay was conducted with ten shortlisted most potent isolates. 68.6%, 58.3% and 66.7% of tested bacterial isolates were capable of P, K, and Zn solubilization, respectively. Klebsiella aerogenes AF3II1 showed the highest P and K solubilization, while isolate AF4II5, AF7II3, and PC3 showed the highest IAA synthesis ability. Serratia plymuthica EDC15 and Pseudomonas putida AF1I1 showed the strongest chitinolytic and siderophore production activity, respectively. Seven isolates demonstrated strong HCN production ability. Five isolates improved carrot seed germination. Only selected isolates with plant growth-promoting properties can improve carrot germination. The results of this study demonstrate that mainly auxins are involved in seed germination. Furthermore, the data suggest that phosphate solubilization ability may play an additional role in seed germination.